DIFFERENCE IN DOPING BEHAVIOR BETWEEN POLYPYRROLE FILMS AND POWDERS - KIM, DY; LEE, JY; KIM, CY; KANG, ET; TAN, KL (ELSEVIER SCIENCE SA, 1995)
The differences in protonation and charge transfer behavior between polypyrrole (PPY) powders and films doped with inorganic acids, such as H2SO4 and HClO4, or bulky acids, such as dodecylsulfonic acid (DS), toluene-4-sulfonic acid (TSA), dodecylbenzensulfonic acid (DBSA) and poly(styrenesulfonic acid) (PSSA), were assessed quantitatively by the X-ray photoelectron spectroscopic (XPS) technique. PPY-dodecylsulfate and PPY-toluene-4-sulfonate films with [N+]/[N] ratio over 40% can be readily prepared electrochemically. Treatment of these salt films with a base results in the 25% deprotonated PPY. Reprotonation of the 25% deprotonated PPY films (containing 25% =N- units) by excess bulky acids readily results in complexes with surface [N+]/[N] ratios substantially above 50%. For deprotonated PPY films loaded with excess inorganic acids, and deprotonated PPY powders loaded with excess simple or bulky acids, the protonation level or [N+]/[N] ratio remains in the order of 25 to 30%. Raman and UV-Vis spectroscopies show little difference in structures of PPY formed chemically and electrochemically, but morphologies of cross sections of the simple and bulky anion-doped samples look different from each other. The enhanced charge transfer interaction in PPY-bulky anion films is probably attributable to the counter-ion-induced molecular 'blending' between the polymer and the dopant.
Keywords: POLYANILINE; POLYMERS; BIPOLARONS; PYRROLE; STATES